Heterogeneous patterns of financial development: Implications for Asian financial integration - Linh Bun; Nirvikar Singh (University of California, Economics Department, 2015)
This paper analyzes detailed differences in patterns of financial development across the major Asian economies, including three of the region's largest economies (China, Japan and South Korea), to understand how these differences might affect possibilities for greater regional financial integration. In particular, the paper argues that heterogeneous patterns of financial development, and not just differences in levels of financial development, may present an economic challenge to regional financial integration efforts, aside from possible political challenges. The paper provides background on the case for financial openness, Asian experiences with financial integration, and regional economic responses to external shocks. It also discusses policy options, including regulatory reform and coordination, and possible risk management policies and institutions, in the context of heterogeneous patterns of financial development.
Keywords: F30; F55; G10; G20; O16; 330; financial development; financial integration; Asia Pacific; East Asia